Framing immigrant integration : Dutch research-policy dialogues in comparative perspective - Scholten, Peter (2011)
Debates on immigrant integration are often caught up in what academics and politicians like to call 'national models of integration'. Researchers and policymakers long for common ground. In the Netherlands, their symbiosis is fed by multiculturalism, something for which Dutch society has long been seen as exemplary. Still, the incorporation of migrants remains one of the country's most pressing social and political concerns. This book thus challenges the idea that there has ever been a coherent or consistent Dutch model of integration. Analysing how immigration is framed and reframed through diverse dialogues, it provides a highly dynamic understanding of integration policy and its evolution alongside migration research. Focus falls on the Netherlands of the past three decades, yet as these findings are held up to the cases of France, Germany and the United Kingdom, insights emerge to more universal questions. Just what are the current political and academic controversies all about? How can governments respond to the challenges of our time? And what contribution can social scientists make?